Blood concentrates for controlling postoperative complications from third molar surgeries: a scoping review - de Almeida, Vinícius Lima; de Assis Costa, Marcelo Dias Moreira; Jesuino, Rômulo Dias; Lima, Lívia Bonjardim; da Silva, Zuleni Alexandre; Lima, Rafael Rodrigues; de Mello Rode, Sigmar [UNESP]; Paranhos, Luiz Renato (FapUNIFESP (SciELO), 2025)
PURPOSE: To map the literature on blood concentrates for managing postoperative sequelae after third molar extraction through a scoping review. METHODS: MedLine, Latin American and Caribbean Health Sciences Literature, Scientific Electronic Library Online, EMBASE, Cochrane Library, Scopus, and Web of Science were the search databases. MedRxiv and EASY provided the grey literature. The investigation included observational studies and clinical trials reporting at least one postoperative sequela. After selecting the articles, the extracted data included study author, year, and country, study design, sample size, age distribution, the type of third molar impaction, flap design, the presence of osteotomy and/or odontosection, co-interventions, blood concentrate type, centrifuge model, centrifugation protocol, collection tubes, outcomes, and the main findings for each outcome. After data extraction, an analysis of the geographic distribution of publications was carried out based on the MapChart website. RESULTS: This review included 63 studies. The leading countries in publications were Turkey, India, and Brazil. Common postoperative sequelae included pain, edema, trismus, alveolar osteitis, and infection. Outcomes varied regarding the effectiveness of concentrates in controlling inflammation, edema, trismus, and alveolar osteitis. Advanced platelet-rich fibrin was the most applied concentrate in recent studies and was associated with reduced edema and trismus. CONCLUSION: All concentrates demonstrated some effectiveness in managing sequelae after third molar extraction, but most did not show significant outcomes in controlling inflammatory signs. It emphasizes the need for further randomized clinical trials and systematic reviews to strengthen the evidence on blood concentrates for managing postoperative sequelae.